PERILAKU MEROKOK REMAJA DI KECAMATAN KANDANGAN: STUDI KUALITATIF TENTANG PERAN KELUARGA DAN TEMAN SEBAYA - Okta Reza, Nia; Iqbal Birsyada, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Smoking behavior among adolescents continues to increase and has become a very serious public health problem, including in suburban areas such as Kandangan District, Temanggung Regency. This study aims to explore in depth the role of the family environment and peer groups in shaping and perpetuating smoking behavior in adolescents. Using a qualitative method with a case study approach, this data was collected through in-depth interviews with seven active adolescent smokers aged 15–18 years in Kandangan District, as well as environmental observations. The results show that the family acts as an